Extending the team component of the Latimer ethical decision-making model for palliative care - Purkis ME; Borycki E; Kuziemsky C; Black F; Cloutier-Fisher D; Fox LA; Mackenzie P; Syme A; Tschanz C (Dove Medical Press, 2011)
Mary Ellen Purkis1, Elizabeth Borycki1,2, Craig Kuziemsky3, Fraser Black4, Denise Cloutier-Fisher5, Lee Ann Fox6, Patricia MacKenzie7, Ann Syme1,8, Coby Tschanz1,41School of Nursing, 2School of Health Information Science, University of Victoria, Victoria, British Columbia; 3Telfer School of Management, University of Ottawa, Ottawa, Ontario; 4Victoria Hospice Society, Victoria, British Columbia; 5Department of Geography, University of Victoria, Victoria, British Columbia; 6Kingston General Hospital, Kingston, Ontario; 7School of Social Work, University of Victoria, Victoria, British Columbia; 8British Columbia Cancer Agency, Vancouver Island Centre, Victoria, British Columbia, CanadaBackground: Each year more than 240,000 Canadians die from terminal and chronic illnesses. It is estimated that 62% of those deaths require palliative care. Palliative care is a specialized domain of health professional team practice that requires discipline-specific knowledge, skills, judgment, and expertise in order to address patient hopes, wishes, symptoms, and suffering. With the emergence of palliative care as a specialized area of interdisciplinary practice, new practice models have also emerged, eg, the Latimer ethical decision-making model for palliative care. The purpose of this research was to undertake a descriptive ethnographic field study of palliative care team practices to understand better the interdisciplinary team communication and the issues that arise when members of different health professions work together as a team.Methods: Study data were collected by observing and videotaping palliative care team meetings. Data were then analyzed using direct content analysis.Results: The study findings substantiated many of the team practice concepts outlined in Latimer's model. Palliative care teams engage in a number of processes that address patient symptoms, suffering, hopes, and plans. However, several new findings also emerged from the data that were not explicit in Latimer's original model. Teams employed five additional emergent team processes when addressing patient symptoms and suffering while attempting to fulfill patient hopes and plans. Those five team processes included explicating practice norms, leadership, provider assumptions, interdisciplinary teaching, and patient safety.Conclusion: Although many team processes have been identified by practice models in the literature, there is a need to study the applicability of these models empirically to validate their representation of aspects of team practice.Keywords: interprofessional team practice, palliative care, ethics, ethnography